Impact of upper tract urothelial carcinoma on response to BCG in patients with non‐muscle‐invasive bladder cancer. (15th February 2021) - Bree, Kelly K.; Hensley, Patrick J.; Brooks, Nathan A.; Matulay, Justin; Li, Roger; Nogueras Gonzalez, Graciela M.; Navai, Neema; Grossman, Herbert Barton; Matin, Surena F.; Dinney, Colin P. N.; Kamat, Ashish M.
Abstract : Objective: To evaluate the impact of upper tract urothelial carcinoma (UTUC) on bacillus Calmette‐Guerin (BCG) response and progression in patients with non‐muscle‐invasive bladder cancer (NMIBC). Patients and Methods: We performed an institutional review board‐approved review of patients with NMIBC treated with adequate intravesical BCG, as defined by the US Food and Drug Administration, at our institution between 2000 and 2018. Patients were stratified by presence of any UTUC and time of UTUC diagnosis (preceding vs synchronous to NMIBC diagnosis or metachronous disease after NMIBC diagnosis). Descriptive statistics were used to summarize the data overall and by groups, and t ‐tests or Wilcoxon's rank sum tests and Pearson's chi‐squared or Fisher's exact tests were used to analyse continuous and categorical data, respectively. Results: Of 541 patients with NMIBC treated with adequate BCG, 59 (10.9 %) were diagnosed with UTUC. Of these, 34 had a history of UTUC prior to NMIBC (UTUC‐P; median [interquartile range IQR] 13.1 [7.4–27.6] months prior), while 25 developed UTUC after diagnosis of NMIBC (six synchronous and 19 metachronous; median [IQR] 12.1 [1.7–28.1] months after). Compared to the non‐UTUC group, patients with UTUC‐P were more likely to exhibit Tis without papillary tumour in the bladder (20.6% vs 5.0%; P < 0.001), but were less likely to have T1 disease on index transurethral resection (8.8% vs 49.4%; P < 0.001). Patients with UTUC‐P developed more recurrences (55.9% vs 34.0%; P = 0.010), any stage/grade progression (23.5% vs 9.8%; P = 0.012) and progression to muscle‐invasive or metastatic disease (17.6% vs 6.4%; P = 0.014). The presence of high‐grade UTUC‐P compared to low‐grade UTUC‐P was associated with increased NMIBC recurrence (68.2% vs 25.0%; P = 0.049). There was no significant difference in rates of recurrence or progression based on timing of UTUC with respect to the index bladder tumour, although this analysis was limited by small numbers. Conclusions: Presence of UTUC prior to a diagnosis of NMIBC was associated with an almost twofold increased recurrence and progression rates after adequate BCG therapy. This should be considered when counselling patients and designing cohorts for clinical trials.